The Effect of Aerobic Exercises on Pain in Patients with Diabetic Peripheral Neuropathy - Naimat-Ullah, Muhammad Sharif Waqas, Umar Sadiq, Amirah Zafar, Afifa Batool (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Evidence has suggested that exercises have always been part of diabetes controlling programs in past and recent years. But recently new improvements have been noticed regarding use of Aerobic exercises in controlling variation in symptoms of diabetes type 2 especially neuropathic pain. It has been proved that Aerobic exercises are much useful in controlling neuropathic symptoms than simple exercises. Objective: This study was to determine the impacts of aerobic exercises on pain in diabetic neuropathic patients. Methodology: A randomized controlled trial was done on 80 patients who fulfilled inclusion criteria of diabetic neuropathy having 40 to 70 years of age with no serious systemic illness and sensitivity. Coin toss method was used to randomize the patients in two groups in the Physical therapy department of District Head Quarter Hospital Layyah, Pakistan. Baseline measurements and demographic data were taken before starting exercise plans. Patients were divided into two groups (group A) treatment group and (group B) control group. Treatment plan consisted on 10 weeks program. Group A was given Aerobic exercises plan like cycling, treadmill walking and Group B was given Strengthening exercises like pulley exercises, dumbbell exercises for a period of 30-minute session thrice a week initially which was later on increased to Four days a week. Data was analyzed through SPSS version 20. Paired t test were used to analyze the data. Results: The Physical Exam score within group showed before treatment 5.53± .91 and after treatment was 1.07±.59 (<0.001*) and it showed significant improvement with the intervention of aerobic groups. Mean difference of pre-test post-test score in strengthening group was 2.19±.40 and in aerobic group was 4.76±2.66 (P=0.010) showed there was significant difference between mean score of both groups. Mean score of pain in aerobic group in measurement was 79.1± 8.9 and after treatment was 39.2± 8.4 (<0.001*) showed significant effect with intervention of this group Conclusion: Aerobic exercises improve the intensity of pain in diabetic neuropathy patients while control group have no improvement of pain. While both experimental and control group showed some improvement regarding muscle tone and strength by exercises but intensity of pain only improved by Aerobic Exercises.